Penggunaan Social Stories untuk Menurunkan Perilaku Nonadaptif Saat Berada dalam Kendaraan Bagi Autisme Dewasa - Markus Nanang Irawan; Sri Widyawati (Philanthropy: Journal of Psychology, 2017)
Individuals autism often have non-adaptive behavioral problems because of their barriers in communication and social interaction. The problem of non-adaptive behavior is often a nuisance to others because its appearance is not appropriate and not in accordance with the environment, age, and expectations of responsibility. One case of non-adaptive behavior that arises is the behavior while in a vehicle where the individual shows the behavior of singing loudly, knocking windows, pinching the driver, even holding the steering wheel. Based on these problems, this study aims to reduce non-adaptive behavior while in a vehicle. Participant is an adult autism. The research method is experiment by giving Social Stories to participants before riding the vehicle then recording to the possibility appearance of non adaptive behavior. The results of graph analysis showed a decrease in non adaptive behavior of adult autism adults while in a vehicle. This study became one of the important studies because it tries to understand the dynamics of behavior problems of individual autisme in adulthood.